Evaluasi Kinerja Yard Occupancy Ratio (YOR) Pelabuhan Tenau, Kupang - Pakpahan, Hartati Mediyanti (ReTII, 2019)
In 2016 container flows at the Port of Tenau Kupang reached the target of 100,000 TEUs. The total loading and unloading of containers at the Port of Tenau Kupang was 115,705 TEUs, whereas in the previous year it was only 99,064 TEUs. The achievement of the container target is due to the passion of business people using containers as a tool for shipping goods on board, due to their high load capacity. The high flow of containers and the limited area of ​​container field facilities need to be balanced with good service management that can expedite the process of entry and entry of containers in the container terminal environment, so as not to cause high utilization of the stacking yard (Yard Occupancy Ratio / YOR). Therefore, this research focuses on evaluating the performance of YOR Port of Tenau Kupang and providing solutions to the evaluation results so that container loading and unloading activities run smoothly. The width of the container stacking field needs in Port of Tenau Kupang in 2017 is 25,271 m2, with a capacity of 23,745 m2 stacking field, so the YOR is 106.43%. This means that the YOR performance of the Port of Tenau Kupang is quite bad, because its achievement is above 10% of the performance standards set by the Director General of Sea Transportation by 60%. To improve YOR performance, the best scenario is to reduce dwelling time to 3 days. Keywords: Yard Occupancy Ratio/ YOR, dwelling time, containers, stacking yard